2004
DOI: 10.1260/0263617043026541
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ammonium Ions onto a Natural Zeolite: Transcarpathian Clinoptilolite

Abstract: A study was carried out of ammonium ion sorption from synthetic aqueous solutions by Transcarpathian clinoptilolite, a natural zeolite, under static conditions. The main physical properties of the clinoptilolite and the basic parameters of its porous structure were determined. Values of the specific surface area and of the pore volume occupied by sorbed substances were calculated using the relative moisture content established and the maximum sorption capacity exhibited towards ammonium ions as well as a nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 10 publications
2
32
2
1
Order By: Relevance
“…Breakthrough and exhaustion capacities for adsorption of NH 4 + ions were 3.36 and 4.26 mg/g (NH 4 + -N/zeolite), respectively. In the literature, q max values have not exceeded 14.82 mg/g for NH 4 + -N (Haralambous et al 1992;Lebedynets et al 2004;Njoroge and Mwamachi 2004), whereas this study reports q max values of 40 mg/g. Therefore, the cost of the pea gravel may be very low, but the longevity, based on the concentration of DSW, will be very short.…”
Section: Permeable Reactive Interceptor Setup and Operationcontrasting
confidence: 83%
“…Breakthrough and exhaustion capacities for adsorption of NH 4 + ions were 3.36 and 4.26 mg/g (NH 4 + -N/zeolite), respectively. In the literature, q max values have not exceeded 14.82 mg/g for NH 4 + -N (Haralambous et al 1992;Lebedynets et al 2004;Njoroge and Mwamachi 2004), whereas this study reports q max values of 40 mg/g. Therefore, the cost of the pea gravel may be very low, but the longevity, based on the concentration of DSW, will be very short.…”
Section: Permeable Reactive Interceptor Setup and Operationcontrasting
confidence: 83%
“…The calculated from the slope and intercept of the linear plot, the maximum amount of exchanged NH 4 + (b) and the Langmuir constant (k) were 9.64 mg g −1 and 0.0548 L mg −1 at 21 • C, respectively. Lebedynets et al [18] and Karadag et al [16] reported that the maximum amount of exchanged NH 4 + using the transcarpathian clinoptilolite and natural Turkish clinoptilolite were 11.5 and 8.12 mg g −1 at 25 • C, respectively. Weatherley and Miladinovic [19] found the ion exchange capacity of New Zealand clinoptilolite for NH 4 + ion as 6.588 mg g −1 .…”
Section: Ion Exchange Isothermsmentioning
confidence: 99%
“…The maximum adsorption capacity of adsorbent (q 0 ) and the adsorption energy coefficient (k) calculated from the slope and the intercept of the linear plot were 8.61 mg/g and 0.044 L/mg at 25 • C, respectively. Lebedynets et al [19] and Karadag et al [10] reported that the maximum amounts of exchanged NH 4 + using the transcarpathian clinoptilolite and natural Turkish clinoptilolite were 11.5 and 8.121 mg/g at 25 • C, respectively. Weatherley and Miladinovic [20] found the maximum amounts of exchanged NH 4 + by New Zealand clinoptilolite and mordenite to be 6.588 and 9.479 mg/g, respectively.…”
Section: Ammonium Ion Exchange Isothermsmentioning
confidence: 99%